Salalens and Salans Derived from 3‐Aminopyrrolidine: Aluminium Complexation and Lactide Polymerisation. Issue 22 (31st May 2019) - Britton, Luke; Ditz, Daniel; Beament, James; McKeown, Paul; Quilter, Helena C.; Riley, Kerry; Mahon, Mary F.; Jones, Matthew D.
Abstract : In this paper a series of 7 salalen ligands based on an aminopyrrolidine backbone have been prepared and characterised. Several systems have been reduced to the salan ONNO type‐ligand. All ligands have been complexed to Al III with Al(1–7 )Me, Al(2a )(O i Pr) and Al(7a )Me being characterised by single‐crystal X‐ray diffraction. In general the Al III centres are best described as being in a trigonal bipyramidal geometry. The solution and solid‐state structures are discussed. All complexes have all been trialled for the production of PLA from rac ‐lactide, the salalen complexes had a preference for heterotactic PLA ( Pr = 0.71), whereas the salan had a more isotactic bias ( Pm = 0.72). In all cases PLA with low dispersities and predictable molecular weights were prepared. The activity of the two classes of ligands is compared with the salan complexes appearing to be significantly more active than the salalen systems. Abstract : A series of Al III complexes with salan and salalen ligands were prepared. These were trialled for the controlled ROP of rac ‐LA. The salan complexes were shown to be significantly more active for the polymerisation.